Biocomposites obtained from wood saw dust using ionic liquids - Croitoru, Catalin; Patachia, Silvia (ACTA CHEMICA IASI, 2014)
The paper presents a new method of wood composites obtaining, as a potential alternative to traditional non-ecological processes involving the use of phenol-based resins. The novelty of the method consists in using only two components, namely wood and an alkylimidazolium chloride ionic liquid. A fraction of wood sawdust dissolves in the ionic liquid, and by water addition it precipitates, acting as a natural binder for the remaining wood particles. FTIR and XRD spectroscopy analysis confirmed the presence of the dominating amorphous cellulose II anomer in the structure of the wood composites. By comparing to the reference, the obtained composites present lower wettability and higher resistance to compression.
Keywords: wood composites; ionic liquids; water absorption; surface energy; FTIR; XRD